Reading Interest and Reading Comprehension : A Correlational Study - Wahyuni Fitria (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2019)
The objective of this research was to find out the correlation between students’ reading interest and reading comprehension. The method used in this study was quantitative and the technique used was a correlational study. The population of the research was taken from students of the eighth grade of SMP Ahmad Dahlan Kota Jambi. The numbers of the population were 47 students. The Total sampling which used all the population was applied as the technique in taking the sample of the research. The data were obtained by using two instruments which were reading interest questionnaires and reading comprehension tests. To measure the correlation Spearman’s Rho was used. The result of this study showed that there was a high correlation between students’ reading interest and their reading comprehension. It was proven by coefficient correlational between students’ reading interest and their reading comprehension was r (0.983), it means those variables were significantly correlated. The result of analyzing the significant value is 0.01, it means that 0.01<0.05, thus, the null hypothesis (Ho) rejected and the alternative hypothesis (Ha) was accepted. Tujuan dari penelitian ini adalah untuk menemukan apakah ada hubungan antara minat baca siswa dan kemampuan membaca mereke. Metode yang di gunakan dalam penelitian ini dengan menggunakan pendekatan kuantitatif melalui penelitian korelasi. Populasi pada penelitian ini adalah seluruh siswa kelas VIII SMP Ahmad Dahlan Kota Jambi. Jumlah populasi adalah 47 siswa. Pengambilan sampel penelitian diperoleh melalui total sampling. Dalam mengumpulkan data, peneliti menggunakan kuesioner untuk mengukur minat baca siswa dan memberikan tes pada siswa untuk mengetahui level pemahaman membaca siswa. Untuk mengukur korelasi peneliti menggunakan teori Spearman’s Rho. Hasil dari penelitian ini menunjukkan bahwa terdapat korelasi yang tinggi antara minat baca dan pemahaman membaca. Terbukti dari hasil perhitungan korelasi ditemukan bahwa hubungan antara minat baca dan pemahaman membaca siswa adalah r (0.983), ini menunjukkan bahwa variabel tersebut memiliki korelasi yang signifikan. Hasil dari signifikansi adalah 0.01, hal ini menunjukkan bahwa 0.01<0.05. Sehingga hipotesa nol (Ho) ditolak dan hipotesa alternatif (Ha) diterimaThe objective of this study was to find out the correlation between reading interest and reading comprehension of the students. Quantitative was used as the approach and the technique used was a correlational study. The eighth grade students of SMP Ahmad Dahlan Kota Jambi were taken as the population. The numbers of the population were 47 students. In taking the sample, total sampling which used all the population was applied as the technique. Reading interest questionnairesand reading comprehension tests were distributed to obtain the data.. Spearman’s Rho was used to measure the correlation. The result showed that there was a high correlation between reading interest and reading comprehension of the students. It was proven by coefficient correlational between those two variables and it was r (0.983). It means that those variables were significantly correlated. The result of analyzing the significant value was 0.01, means that 0.01<0.05. Thus, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted.